Pengaruh Beban Iklan, Harga Transfer Dan Volatilitas Harga Saham Terhadap Agresivitas Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Alisya Athalia; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Tax aggressiveness is an effort to reduce tax burdens, whether through legal or illegal means. This research investigates the relationship between Advertising Expenses, Transfer Pricing, Stock Price Volatility on Tax Aggressiveness with Company Size as a Moderating Variable. The study employs descriptive statistical analysis with a quantitative approach. The findings indicate that Advertising Expenses negatively influence Tax Aggressiveness, while Transfer Pricing and Stock Price Volatility have a positive impact on Tax Aggressiveness. Additionally, Company Size strengthens the influence of Transfer Pricing on Tax Aggressiveness. Company Size weakens the impact of Advertising Expenses and Stock Price Volatility on Tax Aggressiveness